Calibration of the low-cost UAV camera on a spatial test field - Sobura, Szymon (Geodesy and Cartography, 2022)
For several years, the widening range of applications of unmanned aerial vehicles can be noticed not only in the literature review but also in the market of services offered – also in the geodetic sector. While there is a wide range of professional UAVs for aerial mapping tasks, these platforms are expensive. In this study, it was checked whether the calibration of a low-cost drone camera allows for obtaining an accuracy acceptable for photogrammetric studies. For this purpose, a spatial test field was designed on which a multivariate calibration of the UAV camera and control of the obtained results were carried out. Using the elements of the camera’s internal orientation obtained during the calibration process, it was not possible to achieve high accuracy of photogrammetric measurements on control images. This may indicate a problem with the repeatability of determining the elements of internal orientation of the analyzed camera, and thus with the instability of the autofocus system. Nevertheless, the use of the obtained results from the camera calibration as precise approximations of the elements of the camera’s internal orientation had a positive effect on the solution of the image network using the bundle adjustment and the fitting of the spatial model to the ground control points. In addition, the UAV flight over the created spatial test field allowed for a reliable assessment of the possibilities and accuracy that can be obtained on the basis of images from a low-cost drone.